Automatic Pronunciation Scoring for Mandarin Proficiency Test Based on Speech Recognition - Yang Liu; Chunting Yang; Weifeng Ma (2009 International Symposium on Intelligent Ubiquitous Computing and Education : 15-16 May 2009, 2009)
In this paper, a framework for the automatic pronunciation scoring is presented. The system included three modules which are pronunciation parameter database , evaluation model based on artificial neural network and automatic scoring module .The Mandarin proficiency test to be completed by computer-aided evaluation, not only can remove the human factor to establish uniform standards, but also save time, improve efficiency, accelerate the promotion and popularization of Mandarin.